Исфиджаб ғалымдарының ислам мәдениеті мен ғылымының дамуына қосқан үлесі - B., Ilesbekov; Sh., Kerim; A., Zhamashev; E., Alpysbaev (ҚазҰУ хабаршысы. Философия, саясаттану және Мәдениеттану, 2020)
Scientists living in what is now Kazakhstan have made a significant contribution to the development of the Hanafi school fiqh in Central Asia. In particular, these are world-famous scientists from Taraz, Farab, Isfidzhab, Syganak and other cities. Each of them wrote valuable works in various fields of science. This article tells about the life, scientific achievements, labor, religious and government positions of medieval Islamic scholar of Kazakhstan, Ahmad ibn Mansour Al-Isfidzhabi and about other isfidzhabic scientists and their biographies along with classification. The name and number of works of Ahmad ibn Mansour al-Isfidzhabi are specified considering historical and biographical works. Details are provided about how much of his works still in the form of manuscripts and in which libraries they are stored. Considering the fact that Ahmad ibn Mansour al-Isfidzhabi lived in the era of the Karakhanids, his relations with the Karakhan rulers and about the religious and political situations at that time are also discussed. The importance of works of Ahmad ibn Mansour al-Isfidzhabi, his place in the Hanafi school, is confirmed by comparative and analytical methods. At the same time, the possibility of using scientist’s work as basis of the Kazakh school of Islamic сultural studies and introduction into scientific circulation will be discussed. Key words: Culture, law, rule, biography, manuscript.